2014
DOI: 10.23986/afsci.8832
|View full text |Cite
|
Sign up to set email alerts
|

Effect on yield, total phenolic, total flavonoid and total isothiocyanate content of two broccoli cultivars (Brassica oleraceae var italica) following the application of a commercial brown seaweed extract (Ascophyllum nodosum)

Abstract: 28Effect on yield, total phenolic, total flavonoid and total isothiocyanate content of two broccoli cultivars (Brassica oleraceae var italica) following the application of a commercial brown seaweed extract (Ascophyllum nodosum)Theodora Lola-Luz Field experiments were conducted to evaluate the effect of an unfortified extract, of Ascophyllum nodosum on yield and nutritional quality of two broccoli cultivars ('Ironman' and 'Red Admiral'). Total phenolic, total flavonoid, and total isothiocyanates content were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 26 publications
(35 reference statements)
3
23
0
1
Order By: Relevance
“…Foliar sprays at the mid‐ripening stage (MR stage) could modulate biosynthesis of anthocyanins and phenolics, and increase their concentration until harvest, anticipating the achievement of the final concentration of different metabolites. This confirms and explains previous findings of various authors who increased anthocyanins, flavonoids and phenolic compounds in tissues of different plants subjected to applications of A. nodosum extract …”
Section: Discussionsupporting
confidence: 93%
“…Foliar sprays at the mid‐ripening stage (MR stage) could modulate biosynthesis of anthocyanins and phenolics, and increase their concentration until harvest, anticipating the achievement of the final concentration of different metabolites. This confirms and explains previous findings of various authors who increased anthocyanins, flavonoids and phenolic compounds in tissues of different plants subjected to applications of A. nodosum extract …”
Section: Discussionsupporting
confidence: 93%
“…The recorded increase in the total phenolic compounds in the seaweed primed-stressed radish plants is in harmony with the results of Lola-Luz et al (2014), who reported that seaweed extract resulted in increasing of total phenolic compounds in broccoli. This increase could be due to osmotic stress or an increase in plant hormone activities.…”
Section: Discussionsupporting
confidence: 89%
“…According to some authors, application of biostimulants leads to an increase in the levels of phenolic compounds in the edible plant parts (Lola-Luz et al 2013, Ertani et al 2014). Most of the described studies, however, discuss their concentrations immediately after harvest (Lola-Luz et al 2014). However, the research on the effects of biostimulants on the levels of phenolic compounds in vegetables during storage has been very limited.…”
Section: Introductionmentioning
confidence: 99%